Green process engineering : from concepts to industrial applications - Poux, Martine; Cognet, Patrick; Gourdon, Christophe (CRC Press, 2015)
This book has been edited by Martine Poux, Patrick Cognet and Christophe Gourdon from the Laboratoire de Génie Chimique/ENSIACET, Toulouse. It presents an ensemble of methods and new chemical engineering routes that can be integrated in industrial processing for safer, more flexible, economical, and ecological production processes in the context of green and sustainable engineering. Different methods for improving process performance are dealt with, including: Eco-design and process optimization by systemic approaches New technologies for intensification Radical change of industrial processes v.